The Effects of Displacement on Self-employment Survival - Jenny Nykvist (Research Institute of Industrial Economics (IFN), 2008)
A large literature has studied the effect of displacement on labor market outcomes in general, but none has evaluated how the displaced manage as self-employed. This paper studies how the survival of the business is affected by displacement in connection to entry, using a discrete-time proportional hazard model on a matched sample of displaced and non-displaced individuals. The main result of the paper is that, as a consequence of previous displacement, the probability of switching from self-employment to paid employment decreases and the probability of switching to unemployment is unaffected.
Keywords: J24; J63; J65; M13; 330; Self-employment; Survival; Displacement; Kündigung; Selbstständige; Entrepreneurship-Ansatz; Unternehmenserfolg; Schätzung; Schweden